Psychological dynamics among Chinese and British negotiators and translators: A text-analytical study of translation manipulation in the English - Chinese translation of the Treaty of Nanking - Manli Li; Xujun Tian (PLoS ONE, 2025)
This paper examines translation manipulation strategies employed by Chinese and British negotiators and translators in the English Chinese translation of the Treaty of Nanking (1842) and explores the psychological dynamics behind these practices. From the perspective of Lefevere’s translation manipulation theory, the study uncovers how translation served as a tool to mediate power asymmetries and cultural differences between the two parties through a detailed text-analytical approach. The findings highlight deliberate textual manipulations, including rhetorical adjustments omissions, and additions, which reflect the translators’ dual role as mediators and ideological agents. For instance, the Chinese text consistently elevated the Qing emperor’s authority through honorific terms and omitted critical language, aligning the treaty with Qing norms while softening its unfavorable terms. Conversely, the British version emphasized precision and claims of justice, aligning with imperial objectives. Additions in the Chinese version, such as references to imperial approval and justifications for concessions, illustrate attempts to preserve Qing dignity and promote acceptance of the treaty. Overall, the study demonstrates how psychological pressures and power dynamics shaped translation outcomes, offering new insights into translation manipulation, cultural mediation, and the role of translators in constructing historical narratives.